RELATIONSHIP BETWEEN PARENTS' COMMUNICATION AND CONFIDENCE IN STUDENTS OF THE FACULTY OF MEDICINE, TARUMANAGARA UNIVERSITY FOR THE 2020 AND 2021 - Valentzka Sukanto; Anastasia Ratnawati (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Adolescence is a period in which individuals begin to experience rapid growth and development both physically, psychologically, and intellectually. One of the most important things in adolescence is self-confidence. Self-confidence is a belief in the skills and potential in a person. The formation of self-confidence can be influenced by many factors, one of which is parental communication. The purpose of this study was to determine the relationship between parental communication and self-confidence in students of the Faculty of Medicine, Tarumanagara University class of 2020 and 2021. This study used a cross-sectional research design and was an observational analytic study. This research was conducted at the Faculty of Medicine, Tarumanagara University with a total of 154 samples that met the inclusion criteria. Data was taken using a questionnaire. The results of the Pearson Chi-Square test showed that there was a significant relationship between parental communication and self-confidence (p-value 0.002 0.05). So it can be concluded that the higher the level of communication of people, their self-confidence of a person will also be higher. It is recommended that further research can use this research as a reference and can expand the discussion of theories related to this research.